Social norms in pre- Islamic poetry (Antara bin Shaddad as a model): الأعراف الاجتماعية في الشعر الجاهلي (عنترة بن شداد أنموذجاً) (المجلة العربية للعلوم و نشر الأبحاث, 2019)
This research aims to study pre- Islamic literature, an analytical study that reveals the rich social data organized by the poets about his poets, so that his study is not limited to historical analysis, which stands on the definition of the poet and poetic purposes in which he organized.This study came at the forefront of the most important features of the topic; such as the importance of the study, the reasons for its selection, the methodology followed and the plan that followed it.The first topic talked about social norms in Arabic poetry in general with the study of models of them, the second topicIt was a brief definition of the poet Antara bin Shaddad between his name and its origin and qualities and morals, and then came the third topic, which revolved around the social norms addressed by the poet Antara bin Shaddad in his poetry, from the generosity and courage and nobility and chastity and virility and the father of the affliction and humiliation.